Characterizing antiprion compounds based on their binding properties to prion proteins: Implications as medical chaperones. (19th November 2012) - Kamatari, Yuji O.; Hayano, Yosuke; Yamaguchi, Kei‐ichi; Hosokawa‐Muto, Junji; Kuwata, Kazuo
Abstract A variety of antiprion compounds have been reported that are effective in ex vivo and in vivo treatment experiments. However, the molecular mechanisms for most of these compounds remain unknown. Here we classified antiprion mechanisms into four categories: I, specific conformational stabilization; II, nonspecific stabilization; III, aggregation; and IV, interaction with molecules other than PrPC. To characterize antiprion compounds based on this classification, we determined their binding affinities to PrPC using surface plasmon resonance and their binding sites on PrPC using NMR spectroscopy. GN8 and GJP49 bound specifically to the hot spot in PrPC, and acted as "medical chaperones" to stabilize the native conformation. Thus, mechanisms I was predominant. In contrast, quinacrine and epigallocathechin bound to PrPC rather nonspecifically; these may stabilize the PrPC conformation nonspecifically including the interference with the intermolecular interaction following mechanism II. Congo red and pentosan polysulfate bound to PrPC and caused aggregation and precipitation of PrPC, thus reducing the effective concentration of prion protein. Thus, mechanism III was appropriate. Finally, CP‐60, an edarabone derivative, did not bind to PrPC. Thus these were classified into mechanism IV. However, their antiprion activities were not confirmed in the GT + FK system, whose details remain to be elucidated. This proposed antiprion mechanisms of diverse antiprion compounds could help to elucidate their antiprion activities and facilitate effective antiprion drug discovery.